Performance and vibration analyses of lift-offset helicopters using a rigid coaxial rotor - Go, J.-I.; Kim, D.-H.; Park, J.-S; Wie, S.-Y.; Chae, S.-H. (My University, 2017)
The performance, vibration, and load analyses of the XH-59A compound helicopter are validated to establish the analysis techniques for lift-offset compound helicopters using a rigid coaxial rotor. For the performance analysis, this study uses two different analysis codes such as CAMRAD II (Comprehensive Analytical method of Rotorcraft Aerodynamics and Dynamics II) and NDARC (NASA Design and Analysis of Rotorcraft), and for the vibration and load analyses, CAMRAD II is used. Performance analyses using CAMRAD II and NDARC are compared to each other well, and they are also correlated nicely with the flight test results. The 3/rev hub vibratory loads and blade loads of the XH-59A helicopter with auxiliary propulsions are analyzed using CAMRAD II in forward flight and validated reasonably well to the flight test results. Since the present analysis results are in moderate or good agreement with the flight test data, the techniques for performance, vibration, and structural load analyses for lift-offset compound helicopters are established appropriately. Furthermore, the blade section lifts are investigated for the XH-59A with auxiliary propulsions in forward flight to examine the unique characteristics of the ABCTM (Advancing Blade ConceptTM) rotor.